2015
DOI: 10.1002/ange.201500596
|View full text |Cite
|
Sign up to set email alerts
|

Isomerization of Olefins Triggered by Rhodium‐Catalyzed CH Bond Activation: Control of Endocyclic β‐Hydrogen Elimination

Abstract: Five-membered metallacycles are typically reluctant to undergo endocyclic b-hydrogen elimination. The rhodiumcatalyzedisomerization of 4-pentenals into 3-pentenals occurs through this elementary step and cleavage of two CÀHbonds, as supported by deuterium-labeling studies.T he reaction proceeds without decarbonylation, leads to trans olefins exclusively,a nd tolerates other olefins normally prone to isomerization. Endocyclic b-hydrogen elimination can also be controlled in an enantiodivergent reaction on ar ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 54 publications
1
5
0
Order By: Relevance
“…Besides, the double bond could shift. 30 In our experiment, 1-heptene, 2-heptene, and 3heptene could be detected in the decarboxylation of 3-octenoic acid. Therefore, the double bond could shift and 1-heptadecene could be chosen to support the mechanism of aromatization.…”
Section: Energy and Fuelssupporting
confidence: 55%
“…Besides, the double bond could shift. 30 In our experiment, 1-heptene, 2-heptene, and 3heptene could be detected in the decarboxylation of 3-octenoic acid. Therefore, the double bond could shift and 1-heptadecene could be chosen to support the mechanism of aromatization.…”
Section: Energy and Fuelssupporting
confidence: 55%
“…262 Both aryl and alkyl substitution was well-tolerated, and yields and enantioselectivities ranged from 73 to 96% and 91 to 99% ee, respectively. On the basis of related literature reports 264,265 and their own mechanistic studies, Dong and co-workers proposed that the reaction proceeds via an isomerization/hydroacylation sequence. Specifically, oxidative addition intermediate 402 undergoes an intramolecular migratory insertion of an alkene into the Rh− hydride bond, leading to the five-membered rhodacycle 403.…”
Section: C(sp 3 )−H Functionalizationmentioning
confidence: 99%
“…[12] In general, endocyclic b-Helimination of related metallacycles (especially that of 3-to 6-membered rings) are conceived to be extremely challenging. [16] Herein we reported that SCB is an efficient reagent for CÀHb ond silylation [17] under Rh catalysis in the presence of ahindered ligand, possibly enabled by endocyclic b-H elimination of Rh silametallacycles ( Figure 1b). [14] Although DFT calculations suggested that endocyclic b-H elimination might be possible, [15] only af ew examples were reported very recently.…”
mentioning
confidence: 96%